2005
DOI: 10.1007/s10620-005-2564-2
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Alfacon-1 and Ribavirin Versus Interferon ?-2b and Ribavirin in the Treatment of Chronic Hepatitis C

Abstract: Despite advances in the therapy of chronic hepatitis C, a large number of patients do not respond to current therapies. The study objective was to assess whether a combination of interferon (IFN) alfacon-1 and ribavirin improves the response rate compared with a combination of INF alpha-2b and ribavirin in chronic hepatitis C subjects. The study was designed as an open-label, prospective, randomized, controlled study; 128 subjects with chronic hepatitis C were randomized to INF alfacon-1, 15 microg three times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 15 publications
(14 reference statements)
5
28
0
Order By: Relevance
“…This fact might be explained by the small number of patients presenting genotype 1 and low-viral load. Overall, the patients with genotype 1 and high viral load showed an acceptable response rate, which is in accordance to Sjögren et al [11] , showing a higher response rate for this population treated with CIFN and ribavirin instead of pegylated interferon α-2b and ribavirin (46% vs 14%).…”
Section: Discussionsupporting
confidence: 90%
“…This fact might be explained by the small number of patients presenting genotype 1 and low-viral load. Overall, the patients with genotype 1 and high viral load showed an acceptable response rate, which is in accordance to Sjögren et al [11] , showing a higher response rate for this population treated with CIFN and ribavirin instead of pegylated interferon α-2b and ribavirin (46% vs 14%).…”
Section: Discussionsupporting
confidence: 90%
“…The results represent a three to sixfold improvement over the results achieved in prior non-responders utilizing a second course of peg-IFN [4][5][6][7][8][9] and confirm the results of others, who have used c-IFN [24][25][26][27][28][29][30][31][32]. The results are even more noteworthy in that 81% of the patients had a genotype 1 infection, 21% had cirrhosis, and 24% were African American at the initiation of their therapy, factors known to reduce response rates significantly.…”
Section: Discussionsupporting
confidence: 83%
“…Coincident with the increased response rates has been the recognition of the critical value of ribavirin dosing that should continue throughout the treatment program [21,22] and the identification of critical time points that identify a high likelihood of SVR (no HCV at 4 weeks of therapy) or subsequent failure of therapy (HCV positive after 12 weeks of therapy) [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…29 Subsequent prospective studies suggested that CIFN may have a signifi cant advantage over standard IFN, particularly for diffi cult-to-treat patients with higher baseline serum HCV RNA levels and those infected with HCV genotype 1. 30,31 The development of PEG IFN alfa-2a and alfa-2b has resulted in the ability to achieve a substantially higher rate of SVR in naïve patients 6,7 and at this time, a pegylated formulation of CIFN is not available. Although one recent study revealed that CIFN 3 times weekly in combination with weight-based RBV may be as effective as combination PEG IFN alfa-2b and weight-based RBV in the treatment of HCV genotype 1 patients, comparative data are limited.…”
Section: Consensus Interferon In Naïve Patients With Chronic Hepatitis Cmentioning
confidence: 99%